2018
DOI: 10.1371/journal.pone.0200578
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants affecting the use of complementary and alternative medicine in Japan: An analysis using the conceptual framework of social determinants of health

Abstract: This study aims to use the conceptual framework of social determinants of health (SDH) to elucidate the social determinants that affect the use of complementary and alternative medicine (CAM) from the perspectives of both intermediary and structural determinants. Data were derived from a survey mailed to 1,500 randomly selected residents (20–69 years old; May–July 2009) of Sendai city in Japan. A generalized linear model was used in the analysis, with CAM use over the past one month as the dependent variable, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
1
11
1
Order By: Relevance
“…This finding can be explained by the fact that higher SES individuals can afford to buy medicinal herbs due to their higher ability to pay. This observation is consistent with previous studies, in which affordability is one of the most important factors for MH usage [ 17 19 , 31 , 32 ]. A study on the use of herbal medicine in Taiwan indicated that CHM use among pregnant women with a higher level of education and larger income had greater rates of CHM usage [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding can be explained by the fact that higher SES individuals can afford to buy medicinal herbs due to their higher ability to pay. This observation is consistent with previous studies, in which affordability is one of the most important factors for MH usage [ 17 19 , 31 , 32 ]. A study on the use of herbal medicine in Taiwan indicated that CHM use among pregnant women with a higher level of education and larger income had greater rates of CHM usage [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…over the past month. Based on the availability of data in the HIES and previous studies [ 17 19 ], we used the gender of household head, age of household head, education status of household head, a constructed wealth index of households (as a proxy for households’ socioeconomic status), residential area (urban/rural), and development stats of province based on their HDI score (low, middle, and high) as the determinants of MH use in households. Province-level data on HDI was accessed from the Institute for Management Research at Radboud University [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the growing knowledge of and positive attitudes towards the self-management of health and medical care around the world, complementary alternative medicine (CAM) is increasing been widely used by people in Western and Asian countries [ 1 – 3 ]. It has been reported that the one-year prevalence of CAM use among the general population in Europe, the United States, and Japan was 25.9% in 2014, 33.2% in 2012, and 62.1% in 2009, respectively [ 1 – 3 ]. According to an estimation made based on a national survey, the total out-of-pocket expenditures for various types of complementary health approaches in the United States were as high as $30.2 billion [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various types of TCAM among various countries are used by women [1316], middle-aged people [1619], and people with health issues [16, 20–22]. Furthermore, TCAM usage was found to be related to individual psychological determinants including hope [23], health anxiety [24], and belief in the efficacy of TCAM [25, 26]. In addition to these biological and psychological determinants, TCAM usage is also associated with sociological determinants such as culture and customs that surround the healthcare domain.…”
Section: Introductionmentioning
confidence: 99%